Strategi Komunikasi Pencegahan Stunting oleh Puskesmas Palaran - Khumairoh, Ai Syarifah; Nurliah; Sary, Kezia Arum; Rina Juwita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to analyze and describe how the communication strategy of stunting prevention efforts by Palaran Health Center. The formulation of communication strategies uses Onong Uchjana Effendy’s research focus and Campaign Communication Theory. The research method used in this research is descriptive qualitative which aims to explain in detail and in depth. The results of the research conducted by researchers can be concluded that the communication strategy for preventing stunting by the Palaran Health Center is to recognize the target being of communication directly based on data obtained from the posyandu with the target being productive women and adolescents. Indirectly based on followers who are friends and have followed the social media belonging to the Palaran Health Center. Selection of communication media directly by socializing to schools and communities, while indirectly using social media such as Facebook, Instagram, Website and print media such as Leaflets, Banners and Posters. Assessment of the purpose of communication messages based on vision and mission. The role of communicators in communication based on criteria including doctors, nutritionists, health promotion, midwives and nurses.